Filial cannibalism in the Black Stork (Ciconia nigra) - L. S. Cano-Alonso; U. Sellis; E. A. Tamás; B. Kalocsa; B. Janic; D. Pieniak; I. Carbonell; A. Torés; P. Zieliński (The European Zoological Journal, 2024)
Filial and sibling cannibalism have never been documented in Black Storks (Ciconia nigra). We gathered information on 34 breeding events in 10 Black Stork nests from Estonia (three nests), Hungary (two nests), Poland (two nests) and Spain (three nests) being monitored with camera surveillance, live streaming webcams or intensive monitoring control of nests. Overall, we recorded 16 cases of filial infanticide and two cases where the nestlings died by natural causes and were later cannibalized by either their siblings or their parents. Four nestlings were killed by their parents without any attempt of cannibalism. In the remaining 12 cases of infanticide (66.7% of the total losses), 8 nestlings were consumed by one of the parents while in 4 cases the parents were not able to swallow the previously killed nestlings. All victimised nestlings were the youngest, weakest or smallest in their brood. Eight of 14 cases were identified as being associated with environmental stress or an exceptional matter during the breeding season. In at least five cases, one of the mates was new to the nest. Females committing filial infanticide swallowed or tried to swallow the chicks in five out of nine episodes where the parent’s sex was known.